Clinical outcomes and myocardial recovery in energetics, perfusion and contractile function after valve replacement surgery in severe aortic stenosis patients with diabetes comorbidity. (3rd October 2022) - Jex, N; Cubbon, R; Chowdhary, A; Thirunavukarasu, S; Kotha, S; Procter, H; Xue, H; Swoboda, P; Kellman, P; Greenwood, J P; Plein, S; Levelt, E
Abstract: Background: Aortic stenosis (AS) and type 2 diabetes mellitus (DM) are increasingly frequent comorbidities in aging populations, and diabetes is associated with increased morbidity and mortality after aortic valve replacement (AVR). Although distinct pathological entities, AS and DM share common features of impaired myocardial energetics and coronary microvascular dysfunction (CMD). The mechanisms for the adverse prognostic association between AS and DM are incompletely understood. Purpose: Utilising 31phosphorus magnetic resonance spectroscopy (31P-MRS) and CMR, we tested the hypotheses that the collective impact of severe AS and DM on the myocardium aggravates the impairment in energetics, function and perfusion. Methods: Eighty-eight severe AS patients with (AS-DM) and without DM (Iso-AS) undergoing AVR and 15 healthy volunteers were recruited. Patients with coronary artery disease were excluded. Participants with AS underwent 31P-MRS and comprehensive CMR imaging 1 month prior to and 6 months after AVR. Results: Demographic, biochemical and CMR/31P-MRS data are shown in Table-1. All groups were matched for age and sex distribution, with AS groups matched for surgical scores and frailty scores. NTproBNP levels were similarly elevated in AS groups. Left ventricular (LV) volumes and ejection fraction (EF) were similar between the groups, with no significant difference in LV mass or wall thickness between the AS groups. The baseline differences in myocardial energetics, stress myocardial blood flow (MBF) and global longitudinal strain (GLS) are shown in the Figure. AS-DM patients showed greater reductions in myocardial energetics (p<0.0001), global stress MBF (p<0.0001) and more significant reductions in GLS (p=0.001) than the Iso-AS patients. At 6 month post AVR both AS groups showed significant improvements in stress MBF and GLS. However, only the Iso-AS patients showed significant improvement in myocardial energetics. AS patients were followed up for a median of 12 months. Cumulative incidence of the clinical events post AVR (composite of cardiovascular death, stroke, heart failure admission, infective endocarditis) were significantly higher in the AS-DM group than the Iso-AS group (Hazard Ratio: 3.35; 95% CI: 0.97–11.6; p=0.02). Conclusion: Diabetes was associated with increased morbidity and mortality after AVR. We showed for the first time that the collective impact of T2DM and AS on the myocardium aggravates energetic impairment, CMD and contractile dysfunction. While myocardial recovery following AVR was associated with similar improvements in perfusion and contractile function in severe AS patients with and without T2DM, improvements in energetics were only detected in isolated AS patients. However, despite the significant improvements in contractile function and perfusion following AVR in diabetes patients, these parameters remained lower in the group with diabetes comorbidity compared to isolated AS patients. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Wellcome Trust